2020
DOI: 10.1021/acsnano.0c05493
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and Biodegradable Wood Sponge Piezoelectric Nanogenerator for Sensing and Energy Harvesting Applications

Abstract: Developing low-cost and biodegradable piezoelectric nanogenerators is of great importance for a variety of applications, from harvesting low-grade mechanical energy to wearable sensors. Many of the most widely used piezoelectric materials, including lead zirconate titanate (PZT), suffer from serious drawbacks such as complicated synthesis, poor mechanical properties (e.g. brittleness) and toxic composition, limiting their development for biomedical applications and posing environmental problems for their dispo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 51 publications
(103 reference statements)
2
114
0
Order By: Relevance
“…The curve obtained with a loading of 100 kPa shows a much higher energy dissipation than the other two curves, indicating that there is a stress limit for repeating loading events, which is around 45 to 50 kPa for these samples. In previous research, chemical approaches involving, e.g., sodium chlorite, sodium hydroxide, or acetic acid/hydrogen peroxide, have been used to remove lignin and hemicellulose from wood (29,38). Such methods are faster and more efficient than the use of white rot fungi and could result in more compressible wood structures.…”
Section: Resultsmentioning
confidence: 99%
“…The curve obtained with a loading of 100 kPa shows a much higher energy dissipation than the other two curves, indicating that there is a stress limit for repeating loading events, which is around 45 to 50 kPa for these samples. In previous research, chemical approaches involving, e.g., sodium chlorite, sodium hydroxide, or acetic acid/hydrogen peroxide, have been used to remove lignin and hemicellulose from wood (29,38). Such methods are faster and more efficient than the use of white rot fungi and could result in more compressible wood structures.…”
Section: Resultsmentioning
confidence: 99%
“…The maximum instantaneous power density obtained by fabricated PENG is larger than the previously reported PVDF/AlO‐rGO composite PENG by Karan et al and many others and the comparative tabulated forms are shown in Supporting Information T1. [ 55–60 ] Frequency‐dependent output voltage performance is also observed from 1 to 6 Hz of the fabricated PENGs by finger imparting (imparting force ≈28 N), as shown in Figure 5f. Maximum output voltage has been obtained at 6 Hz frequency.…”
Section: Resultsmentioning
confidence: 90%
“…OPEN ACCESS Niu et al, 2020;Najjar et al, 2017;Saravanakumar et al, 2015;Sun et al, 2020a;Sun et al, 2020b;Wang et al, 2017). In addition to serving as a power source, biocompatible nanogenerators can also be used as a sensor, such as a pressure sensor or chemical sensor (Khandelwal et al, 2019;Kim et al, 2018b;Qian et al, 2019;Saravanakumar et al, 2015 (Saravanakumar et al, 2015).…”
Section: Llmentioning
confidence: 99%
“…Figure9. Biocompatible nanogenerators for energy harvesting (A and B) (A) A diagram of wood sponge-based PENG and (B) its application in a self-powered system(Sun et al, 2020a). (C-E) Flexible and transparent TENGs served as body movement sensors, which clearly distinguished motions of a foot, ankle, knee, wrist, and neck(Kim et al, 2018b).…”
mentioning
confidence: 99%